Pelatihan Pembuatan Game Edukasi WordWall Bagi Guru SMA Dharma Amiluhur Yogyakarta - Nafida Hetty Marhaeni; Ichlasia Ainul Fitri; Naela Faza Fariha (Universitas Lancang Kuning, 2023)
This community service aims to provide training on creating a WordWall educational game for teachers at SMA Dharma Amiluhur, Sedayu, Special Region of Yogyakarta. The training was held in May at the school and was attended by 25 teachers of all subjects. This activity begins with an introduction regarding the types of educational games, the advantages and disadvantages of each educational game, and the latest developments related to the benefits of using educational games for learning. In addition, this service is also focused on providing knowledge and understanding to teachers at Dharma Amiluhur High School regarding the benefits of the WordWall educational game, the features on the website and how to make it. The results of the dedication show that the success indicators have been achieved, namely ≥75% of teachers understand the benefits and features of WordWall, attendance at each meeting is 80%, and all teachers can make educational games WordWall with various features available even in learning that takes place after training, teachers at SMA Dharam Amiluhur have used the educational game WordWall as a learning evaluation website that students must work on. Therefore, this community service has achieved the set indicators of success and the goal of making teachers at the school able to understand and use the WordWall educational game has been achieved.